Management of Respiration by Arranging Tongue Position with a Modified Feeding Plate on a Pierre Robin Syndrome Patient: Case Report - Sema Akpınar; Hüsamettin Oktay; Abdülvahit Erdem (Galenos Yayinevi, 2010)
In this case report, glossoptosis treatment of a newborn with PRS and her preparation for palatoplasty with a conservative method is presented.